Brain Responses to Food Choices and Decisions Depend on Individual Hedonic Profiles and Eating Habits in Healthy Young Women - Coquery, Nicolas; Gautier, Yentl; Serrand, Yann; Meurice, Paul; Bannier, Elise; Thibault, Ronan; Constant, Aymery; Moirand, Romain; Val-Laillet, David (Frontiers in Nutrition, 2022)
The way different food consumption habits in healthy normal-weight individuals can shape their emotional and cognitive relationship with food and further disease susceptibility has been poorly investigated. Documenting the individual consumption of Western-type foods (i.e. high-calory/sweet/fatty/salty) in relationship with psychological traits and brain responses to food-related situations can shed light on the early neurocognitive susceptibility to further diseases and disorders. We aimed here to explore in a population of 50 healthy normal-weight young women the relationship between eating habits, psychological components of eating, and brain responses as measured with BOLD fMRI during a cognitive food-choice task and with functional connectivity (FC) during resting state fMRI (rsfMRI). A food consumption frequency questionnaire (FCFQ) was used to classify them on the basis of their eating habits and preferences with a principal component analysis (PCA). Based on the PCA, we defined two eating habit profiles defined as Prudent-type consumers (PTc, N=25) and Western-type consumers (WTc, N=25), i.e. respectively low- and high-consumers of WD foods. The first two PCA dimensions, PCA1 and PCA2, were associated with different eating psychological components and brain responses in regions involved in reward and motivation (striatum), hedonic evaluation (orbitofrontal cortex, OFC), decision conflict (anterior cingulate cortex, ACC), and cognitive control of eating (prefrontal cortex). PCA1 was inversely correlated with the FC between the right nucleus accumbens and the left lateral OFC, while PCA2 was inversely correlated with the FC between the right insula and the ACC. Our results suggest that among a healthy population, distinct eating profiles can be detected, with specific correlates in the psychological components of eating behavior, which are also related to a modulation in the reward and motivation system during food choices. We could detect different patterns in brain functioning at rest, with a reduced connectivity between the reward system and the frontal brain region in Western-type food consumers, which might be considered as an initial change towards ongoing modified cortico-striatal control.